(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Everyone agrees that employee motivation is a major component in how well a company does. The major goal of this research was to find out how different motivating variables, such as pay, recognition, working environment, leadership, and job satisfaction, affect productivity in the workplace. Using a quantitative research approach, a sample of one hundred workers were surveyed using structured questionnaires to gather primary data. We used inferential methods including the Chi-square test and ANOVA, as well as descriptive statistics and correlation analysis, to look at the data. The results revealed that salary, appreciation, and favorable working conditions are key motivators that influence employee performance positively. Furthermore, the study found that leadership behavior plays an essential role in enhancing employee motivation. Despite a significant number of employees reporting neutrality regarding satisfaction with company management, most respondents agreed that motivation from officers, proper recognition, and a positive organizational environment directly contribute to improved performance. Based on the findings, the study recommends that organizations invest in fair compensation, foster supportive leadership, improve working conditions, and establish clear promotion policies to sustain high motivation levels.